Hölder continuity and upper estimates of solutions to vector quasiequilibrium problems - Li, S.; Chen, C.; Li, X.; Teo, Kok Lay (Elsevier BV * North-Holland, 2011)
In this paper, we establish the Hölder continuity of solution mappings to parametric vector quasiequilibrium problems in metric spaces under the case that solution mappings are set-valued. Our main assumptions are weaker than those in the literature, and the results extend and improve the recent ones. Furthermore, as an application of Hölder continuity, we derive upper bounds for the distance between an approximate solution and a solution set of a vector quasiequilibrium problem with fixed parameters.